Partnerships in global health and collaborative governance: lessons learnt from the Division of Tropical and Humanitarian Medicine at the Geneva University Hospitals. Issue 1 (December 2016) - Beran, David; Aebischer Perone, Sigiriya; Alcoba, Gabriel; Bischoff, Alexandre; Bussien, Claire-Lise; Eperon, Gilles; Hagon, Olivier; Heller, Olivia; Jacquerioz Bausch, Frédérique; Perone, Nicolas; Vogel, Thomas; Chappuis, François
Abstract Background In 2007 the "Crisp Report" on international partnerships increased interest in Northern countries on the way their links with Southern partners operated. Since its establishment in 2007 the Division of Tropical and Humanitarian Medicine at the Geneva University Hospitals has developed a variety of partnerships. Frameworks to assess these partnerships are needed and recent attention in the field of public management on collaborative governance may provide a useful approach for analyzing international collaborations. Methods Projects of the Division of Tropical and Humanitarian Medicine were analyzed by collaborators within the Division using the model proposed by Emerson and colleagues for collaborative governance, which comprises different components that assess the collaborative process. Results International projects within the Division of Tropical and Humanitarian Medicine can be divided into four categories: Human resource development; Humanitarian response; Neglected Tropical Diseases and Noncommunicable diseases. For each of these projects there was a clear leader from the Division of Tropical and Humanitarian Medicine as well as a local counterpart. These individuals were seen as leaders both due to their role in establishing the collaboration as well as their technical expertise. Across these projects the actual partners vary greatly. This diversity means a wide range of contributions to the collaboration, but also complexity in managing different interests. A common definition of the collaborative aims in each of the projects is both a formal and informal process. Legal, financial and administrative aspects of the collaboration are the formal elements. These can be a challenge based on different administrative requirements. Friendship is part of the informal aspects and helps contribute to a relationship that is not exclusively professional. Conclusion Using collaborative governance allows the complexity of managing partnerships to be presented. The framework used highlights the process of establishing collaborations, which is an element often negated by other more traditional models used in international partnerships. Applying the framework to the projects of the Division of Tropical and Humanitarian Medicine highlights the importance of shared values and interests, credibility of partners, formal and informal methods of management as well as friendship.